K-F zeolite nanocrystals synthesized from organic-template-free precursor mixture - Wong, Siew Fang; Awala, Hussein; Vincente, Aurélie; Retoux, Richard; Ling, Tau Chuan; Mintova, Svetlana; Mukti, Rino R.; Ng, Eng Poh (Elsevier, 2017)
K-F zeolite nanocrystals (structure code EDI) are synthesized from a template-free Al 2 O 3 –SiO 2 –K 2 O–H 2 O precursor system. The use of a very reactive organic-template-free gel system (4SiO 2 : 1Al 2 O 3 : 16K 2 O: 160H 2 O) enables the crystallization of EDI-type nanosized zeolite to accomplish within 3 h at 100 °C. The K-F zeolite crystals have flattened cuboid shape morphology (ca. 27 nm) and they tend to agglomerate and form secondary spherical particles (ca. 310 nm). The K-F zeolite nanocrystals have high alumina content (Si/Al ratio = 1.10) and high crystalline solid yield (79%) offering a promising route for large-scale production of hydrophilic zeolite nanoparticles.